The signed image. - Walter Phillips Gallery, The Banff Centre School of Fine Arts, Banff (Banff : Walter Phillips Gallery - The Banff Centre for the Arts Banff, 1986)
Fukawa, Hiro ; Duchesneau, Mario ; Plourde, Joanne ; Poisson, Denise ; Albertson, Constant ; Anderson, Danae ; Amundson, Garth ; Brown, David ; Butler, Niamh ; Dean, Christ ; Dubeau, Madeleine ; Duchesneau, Mario ; Edmonson, Greg ; Fukawa, Hiro ; Gour, Pierre ; etc.
The signed image, Walter Phillips Gallery - The Banff Centre for the Arts Banff, March 20 - March 31, 1986
boek